2022
DOI: 10.1136/openhrt-2022-002072
|View full text |Cite
|
Sign up to set email alerts
|

Association between operator volume and mortality in primary percutaneous coronary intervention

Abstract: BackgroundThere is a paucity of real-world data assessing the association of operator volumes and mortality specific to primary percutaneous coronary intervention (PPCI).MethodsDemographic, clinical and outcome data for all patients undergoing PPCI in Leeds General Infirmary, UK, between 1 January 2009 and 31 December 2011, and 1 January 2013 and 31 December 2013, were obtained prospectively. Operator volumes were analysed according to annual operator PPCI volume (low volume: 1–54 PPCI per year; intermediate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…9 Several studies demonstrated that higher-volume PCI operators and institutions have better clinical outcomes, including mortality. [9][10][11] In our study, versus 3.7 (0.6−7.3), respectively. 12 Our findings indicate that CTO PCI operators are often highly experienced in managing complications, which might be due to CTO operators performing more PCIs and more challenging cases, and experiencing complications more frequently.…”
Section: Pci Volume and Complicationssupporting
confidence: 40%
See 1 more Smart Citation
“…9 Several studies demonstrated that higher-volume PCI operators and institutions have better clinical outcomes, including mortality. [9][10][11] In our study, versus 3.7 (0.6−7.3), respectively. 12 Our findings indicate that CTO PCI operators are often highly experienced in managing complications, which might be due to CTO operators performing more PCIs and more challenging cases, and experiencing complications more frequently.…”
Section: Pci Volume and Complicationssupporting
confidence: 40%
“…An analysis of the National Cardiovascular Data CathPCI registry performed between 2009 and 2015 found that the median number of annual PCIs per operator was 59 (21−106) 9 . Several studies demonstrated that higher‐volume PCI operators and institutions have better clinical outcomes, including mortality 9–11 . In our study, operators had higher PCI volume 205 (105−328) compared with the average interventionalist.…”
Section: Discussionmentioning
confidence: 51%